2000
DOI: 10.1038/sj.gt.3301140
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-targeted in vivo gene expression by intravenous injection of plasmid DNA complexed with synthetic multi-functional gene delivery system

Abstract: To achieve hepatocyte-targeted in vivo gene expression, a carrier that controls both the tissue and intracellular distribution of DNA was designed and synthesized. A cationic polymer, poly(L-ornithine) (pOrn), was modified first with galactose, then with a fusigenic peptide (mHA2) to obtain GalpOrn-mHA2. When applied with Gal-pOrn-mHA2 to asialoglycoprotein receptor-positive cells, fluorescein-labeled DNA showed a diffuse profile, suggesting the release of DNA from endosomes and/or lysosomes by the carrier. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 39 publications
(34 reference statements)
1
80
0
Order By: Relevance
“…161 When incorporated into an ASOR-targeted gene delivery polymer, the HA2 peptide enhanced gene transfer to the liver 300-fold higher than complexes lacking the HA2 peptide. 162 The authors reported observations that the peptide induced diffusion of the complex into the cytoplasm, suggesting that gene transfer enhancement was due to HA2-induced endosomolysis.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…161 When incorporated into an ASOR-targeted gene delivery polymer, the HA2 peptide enhanced gene transfer to the liver 300-fold higher than complexes lacking the HA2 peptide. 162 The authors reported observations that the peptide induced diffusion of the complex into the cytoplasm, suggesting that gene transfer enhancement was due to HA2-induced endosomolysis.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Of these, the release of pDNA from endosomes/lysosomes into the cytoplasm after internalization is a major obstacle for efficient gene expression in hepatocytes. Therefore, manipulation of this process by functional peptides or the use of PEI with pH buffering functions in lysosomes [53] by galactosylated macromolecules might allow high transfection rates in vivo [40,49,[54][55][56]. Our group developed a mannosylated macromolecular carrier system for cell-selective targeting based on dextran, which has high solubility, an abundance of hydroxyl groups for chemical modification, low immunogenicity, and is used in the clinic as a plasma expander [2].…”
Section: Glycosylated Macromolecules For Cell-selective Targetingmentioning
confidence: 99%
“…Separation of the liver cells revealed that such complexes were preferentially taken up by hepatocytes, the cells possessing asialoglycoprotein receptors. When the transfection efficiency of the pDNA/galactosylated polymer complex was boosted by the use of a fusogenic peptide (an acid-sensitive peptide designed based on the amino-terminal of influenza virus hemagglutinin subunit HA-2 or mHA2), the amount of transgene product in the hepatocytes accounted for over 95% of the total amount in all the tissues examined, 23) indicating the success of this target cell-specific gene transfer in vivo. Figure 3 summarizes the tissue disposition of pDNA and transgene expression following intravenous injection of pDNA complexed with a hepatocyte-targeted polymeric carrier in mice.…”
Section: Selection Of Administration Routementioning
confidence: 99%
“…The transfection efficiency into mouse liver was enhanced by the covalent binding of a fusogenic peptide to a hepatocyte-specific pDNA complex. 23) Another approach involves the use of a vector with a high buffering capacity and the ability to swell when protonated. Such a system, e.g.…”
Section: Level Of Transgene Expressionmentioning
confidence: 99%
See 1 more Smart Citation